DIAGNOSTIC ACCURACY OF ENDOMETRIAL CURETTAGE IN ENDOMETRIAL PATHOLOGY - Saadia, Aiza; Mubarik, Azher; Zubair, Alia; Jamal, Shahid; Zafar, Ambreen (Journal of Ayub Medical College Abbottabad, 2011)
Background: Abnormal uterine bleeding is one of the most frequent problems in life of an adult female. Uterine curettage or biopsy remains a preferred sampling procedure for diagnosis of the endometrial pathology. The objective of this study was to compare the sensitivity, specificity, positive and negative predictive value of endometrial curettage. Patients and Methods: This validation study was carried out at the Department of Histopathology, Army Medical College Rawalpindi in collaboration with Military Hospital, Rawalpindi from January to December 2010. The study included 50 curettage and subsequent hysterectomy specimen of the same patients. Non-probability sampling technique was used to divide patients into two groups with 50 patients in each group. One group was of endometrial curettage having endometrial pathology (group A). Second group was of subsequent hysterectomy specimen of the same patients (group B). Results: Endometrial curettage was found most accurate in diagnosing endometrial carcinoma. Sensitivity of endometrial curettage was found to be 33% whereas specificity and positive predictive value was found to be 100% each. Negative predictive value was found to be 93.1%. Conclusion: Endometrial biopsy is a sensitive and a specific test in and is accurate in diagnosing endometrial pathology. It is found most accurate in diagnosing endometrial carcinoma. Keywords: Dilation and curettage, Hysterectomy, Hormone imbalance, endometrium, dysfunctional uterine bleeding, DUB